2022
DOI: 10.1002/cmdc.202200251
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid‐β Inspired Short Peptide Amphiphile Facilitates Synthesis of Silver Nanoparticles as Potential Antibacterial Agents

Abstract: An amyloid‐β inspired biocompatible short peptide amphiphile (sPA) molecule was used for controlled and targeted delivery of bioactive silver nanoparticles via transforming sPA nanostructures. Such sPA‐AgNPs hybrid structures can be further used to develop antibacterial materials to combat emerging bacterial resistance. Due to the excellent antibacterial activity of silver, the growth of clinically relevant bacteria was inhibited in the presence of AgNPs‐sPA hybrids. Bacterial tests demonstrated that the high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 58 publications
1
28
0
Order By: Relevance
“…The high‐resolution TEM image (Figure 8E, inset) of AgNPs showed that d spacing was 2.6 Å along with the selected area electron diffraction (SAED) pattern and indexing of rings as (111), (200), (220), and (311) also confirmed polycrystalline and fcc nature of AgNP (Figure 8F). This is in good agreement with reported literature [24,25] . A such drastic change in morphology of sPA2 nanostructures (Figure 1F and 2 B) in the presence of AgNPs is perhaps due to shuffled key amino acid sequence in sPA2 .…”
Section: Methodssupporting
confidence: 93%
See 3 more Smart Citations
“…The high‐resolution TEM image (Figure 8E, inset) of AgNPs showed that d spacing was 2.6 Å along with the selected area electron diffraction (SAED) pattern and indexing of rings as (111), (200), (220), and (311) also confirmed polycrystalline and fcc nature of AgNP (Figure 8F). This is in good agreement with reported literature [24,25] . A such drastic change in morphology of sPA2 nanostructures (Figure 1F and 2 B) in the presence of AgNPs is perhaps due to shuffled key amino acid sequence in sPA2 .…”
Section: Methodssupporting
confidence: 93%
“…Therefore, an alternative approach is needed to minimize the toxic effects of AgNPs. Based on available reports and our lab protocols regarding the synthesis of metal nanoparticles, sPA1 and 2 exhibits the potential to synthesize AgNPs by facile method [24–27] . Hence, to prepare AgNPs with help of sPA1 and 2 , 200 μM solution of each sPA with 200 μM of Ag(I) ions were incubated in sunlight for 5–10 minutes [24,28] …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…70 This mortise-tenon joint is independent of the properties of the material encapsulated inside the polymer, and with this advantage, nanostructures with a discrete number of ligands (i.e., peptides) can be obtained by gel electrophoresis. 71 Such peptide/protein-nanoparticle 72 hybrid building blocks hold great potential for bottom-up origami-like nanofabrication, with which Parak and co-workers demonstrated the signicant differences of nanoparticles conjugated with a different number of antibodies in tumor-targeting therapy. 73 Articial light-harvesting complexes have been a hot spot to use "innite" light energy due to the depleting fossil fuels such as coal, oil and natural gas.…”
Section: Discussionmentioning
confidence: 99%